2020
DOI: 10.1108/gs-12-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Research on faculty and staff for constructing the “double first-class” universities based on Grey–AHP comprehensive evaluation model

Abstract: PurposeIn order to improve the competitiveness of the “double first-class” university in China, it is essential to conduct a rational, scientific study of the current status of the staff to ensure its long-term development.Design/methodology/approachBased on the grey analytic hierarchy process (Grey–AHP), this paper evaluates the situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…They have made various improvements to it to increase the accuracy and comprehensiveness of evaluation. Based on the grey analytic hierarchy process (Grey-AHP), Sun (2020) evaluated the situation of faculty and staff, hereby, analyzed the initiative and enthusiasm of faculty and staff in the construction of “double first-class universities”. Yan et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have made various improvements to it to increase the accuracy and comprehensiveness of evaluation. Based on the grey analytic hierarchy process (Grey-AHP), Sun (2020) evaluated the situation of faculty and staff, hereby, analyzed the initiative and enthusiasm of faculty and staff in the construction of “double first-class universities”. Yan et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it plays a very important role in the national "double first-class" initiative. Sun [10] evaluated the status of faculty and staff using the (Grey-AHP) model, and concluded that these factors also play an important role in accomplishing the initiative of "first-class" universities. They suggested that to improve the competitiveness in Chinese "double-class" universities, it is necessary to conduct rational and scientific research, examining the current status of the staff.…”
Section: "Double First-class" Construction Initiative and University ...mentioning
confidence: 99%
“…The main reason behind the criticism was the excessive inclusion of the numbers and making it more complex to deal with uncertain and vague decision-making situations. Hence, to make computations easier than fuzzy numbers and also consider the expert's subjectivity while giving their preferences, the present study has proposed the Grey theory-based AHP and OCRA hybrid MCDM technique for evaluating the HCWTF location candidates ( Sun, 2020 ). OCRA was initially proposed by Parkan (1994) to evaluate the operational competitiveness of the productions units.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the present study proposes a new hybrid MCDM methodology (AHP and OCRA), based on grey theory to handle the vagueness in the decisions analysis. The main advantages of adopting the hybrid Grey-AHP-OCRA methodology are: Grey theory well captures the fuzziness and uncertainty in the experts’ opinion ( Thakur and Anbanandam, 2015 ); Grey scale is an appropriate tool to collect the opinion of few stakeholders involved in the decisions making ( Kumar and Anbanandam, 2020 ); integrating AHP technique will help in accumulating the experience and knowledge of the field experts by taking their subjective preferences on prioritizing the criteria weights ( Sun, 2020 ; Ulutaş, 2019 ); OCRA methodology can handle the MCDM situations, where the criteria weights are depending on the alternatives and also when all the criteria are not applicable on all the alternatives (Parkan, 1994); and using OCRA, different weight distributions can be given to criteria for different alternatives ( Parkan, 2006 ).…”
Section: Literature Reviewmentioning
confidence: 99%